2012
DOI: 10.1242/jeb.065961
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3: cryoprotection and glycogen metabolism in the freeze-tolerant wood frog

Abstract: SUMMARYThe terrestrial anuran Rana sylvatica tolerates extended periods of whole-body freezing during the winter. Freezing survival is facilitated by extensive glycogen hydrolysis and distribution of high concentrations of the cryoprotectant glucose into blood and all tissues. As glycogenesis is both an energy-expensive process and counter-productive to maintaining sustained high cryoprotectant levels, we proposed that glycogen synthase kinase-3 (GSK-3) would be activated when wood frogs froze and would phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 50 publications
(59 reference statements)
2
19
0
1
Order By: Relevance
“…Three Coomassie-stained bands that did not differ in intensity between active and frozen conditions were used to normalize the corresponding intensity of the immunoreactive band in each lane to correct for any unequal protein loading, as described previously (Dieni, Bouffard & Storey, 2012). Our group typically opts to follow this method of protein normalization, instead of probing for “conventional” loading controls such as actin or tubulin, for all our stress-physiology and adaptation studies (Abboud & Storey, 2013; Lama, Bell & Storey, 2013; Rouble et al, 2013); this is an increasingly-common practice in other groups (Goldberg et al, 2013; Bahar et al, 2014; Da’dara et al, 2014), particularly in instances where levels of housekeeping proteins themselves are suspected of changing due to pharmacological, pathophysiological, or physiological stress (Li et al, 2011; Eaton et al, 2013; Parrondo et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three Coomassie-stained bands that did not differ in intensity between active and frozen conditions were used to normalize the corresponding intensity of the immunoreactive band in each lane to correct for any unequal protein loading, as described previously (Dieni, Bouffard & Storey, 2012). Our group typically opts to follow this method of protein normalization, instead of probing for “conventional” loading controls such as actin or tubulin, for all our stress-physiology and adaptation studies (Abboud & Storey, 2013; Lama, Bell & Storey, 2013; Rouble et al, 2013); this is an increasingly-common practice in other groups (Goldberg et al, 2013; Bahar et al, 2014; Da’dara et al, 2014), particularly in instances where levels of housekeeping proteins themselves are suspected of changing due to pharmacological, pathophysiological, or physiological stress (Li et al, 2011; Eaton et al, 2013; Parrondo et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular freezing and any resulting irreparable damage to cellular contents is prevented by natural cryoprotection; liver glycogen stores undergo extensive hydrolysis (causing a decrease in liver mass by approximately 45%), and glucose is exported and systemically distributed, accumulating in some tissues at levels up to 40–60 times higher than euglycemic levels (Storey & Storey, 1985; Costanzo, Lee & Lortz, 1993). Such a broad reorganization requires numerous modulations at several levels of the signaling and metabolic hierarchy of glucose metabolism, including: (1) phosphorylation and sustained activation of liver glycogen phosphorylase (Crerar, David & Storey, 1988; Mommsen & Storey, 1992); (2) adaptations to plasma membranes in order to facilitate glucose transport and distribution (King, Rosholt & Storey, 1993); (3) tissue-specific adjustment of anabolic and catabolic signaling pathways (e.g., the insulin/Akt pathway, and the adenosine monophosphate-activated protein kinase or AMPK pathway) to optimize glucose production, distribution, uptake, and utilization as a cryoprotectant (Rider et al, 2006; Dieni, Bouffard & Storey, 2012; Zhang & Storey, 2013; do Amaral, Lee & Costanzo, 2013), and; (4) suppression of metabolic pathways that would otherwise divert glucose away from cryoprotection (e.g., pentose phosphate pathway, glycolysis; Dieni & Storey, 2010; Dieni & Storey, 2011), among others. Following the return of warmer temperatures and the arrival of spring, frogs thaw and resume their natural life cycle with no apparent debilitating results of the freeze-thaw process.…”
Section: Introductionmentioning
confidence: 99%
“…The K m obtained in this study is similar to those determined in studies that utilized other detection techniques. For instance, a study of wood frog GSK3 found the K m peptide to be 23 ± 4 μM when utilizing radioactive ATP and subsequent detection of radiolabelled peptides on a phosphor screen [7]. In addition to the seemingly accurate K m curve generated, the ChemiGenius Bioimaging system provided a unique ability to visualize the end point luminescence after the kinase reaction (Fig.…”
Section: Additional Informationmentioning
confidence: 99%
“…It inhibits some transcription factors like the forkhead family and the Peroxisome proliferator-activated receptor-gamma coactivator-1α (PGC-1α) leading to a decrease in the activity of Glucose-6-phosphatase (G6Pase), a key enzyme implicated in hepatic glucose production [16, 17]. On the other hand, insulin signaling phosphorylates glycogen synthase kinase-3 (GSK-3) leading to the activation of glycogen synthase (GS), a key enzyme implicated in glucose storage [18]. In addition, insulin regulates glucose uptake and utilization in muscle through the stimulation of glucose transporter 4 (GLUT4) translocation to the plasma membrane in order to mediate facilitative glucose diffusion [19].…”
Section: Introductionmentioning
confidence: 99%